Language awareness as a prerequisite of literacy skills - Kucharská, Anna; Špačková, Klára; Šmejkalová, Martina (LingBaW. Linguistics Beyond and Within, 2022)
Monitoring children’s language ability levels makes it possible to predict their school achievement and identify potential difficulties. Identifying literacy difficulties in terms of specific learning disabilities is an important topic for elementary school pupils. Today, there is a general consensus based on research evidence that the diagnostic battery of literacy skills should always include a test of language abilities, through which the prerequisites for individual reading skills and at-risk readers can be identified. A working group has created a diagnostic tool for language awareness that allows the morphological-syntactic (subtest A and B) and semantic (subtest C) language levels of Czech children of elementary school age to be assessed. Data analysis examines how individual language skills correspond to reading performance – decoding and reading comprehension in different reading modalities (oral and silent reading) and how they correspond to other prerequisites for reading, such as listening comprehension. The paper introduces a new diagnostic tool using a quantitative methodology. It is based on data from the research project Key Literacy Skills for Primary School Pupils – a diagnostic battery, in which 881 elementary grade pupils (Grade 1 – Grade 5) participated. The statistical parameters of the new tool are presented and the relations between the Language Awareness Test, decoding skills, and oral and silent reading comprehension are analysed.